Factor Affecting the Acceptance of Online Learning by Primary School Teachers During the Covid -19 Pandemic: A Structural Study Using the unified theory of acceptance and use of technology (UTAUT) Model - Dastjerdi, Negin (ASEAN Journal of Educational Research and Technology, 2023)
The present study has sought to provide a structural model of the relationships between the influencing factors in the acceptance of e-learning by teachers during the Covid-19 pandemic, based on the unified theory of acceptance and use of technology (UTAUT) model. The research method was descriptive and correlational. The statistical population of this research involved all primary school teachers in Isfahan, Iran, from which 250 primary teachers were randomly selected as samples using Morgan’s table. The tool used included a researcher-made questionnaire based on the technology acceptance and application model. The findings were analyzed using PLS statistical software. As the results showed, the UTAUT model of the factors affecting teachers’ acceptance of e-learning during the Covid-19 pandemic has a good fit. Therefore, performance expectancy, effort expectancy, social influence, hedonic motivation, price value, and facilitating conditions had a direct and significant effect on teachers’ behavioral intention to use E-learning. It was also observed that user intention has a mediating role in the relationship between the mentioned variables and teachers’ use of online education. Therefore, it can be stated that the findings confirm the theoretical foundations of the UTAUT model.